7. The Consideration of Halalan, Thayyiban and Economic Factor of Consuming Chicken Meat in Several Markets of Aceh Besar District - Teuku Shaddiq Rosa; Teuku Reza Ferasyi; Razali Razali; Hamdani Budiman; Fachrurrazi Fachrurrazi; Nurliana Nurliana (Universitas Syiah Kuala, 2018)
This study was aimed to determine the basic consideration of consumers belief on halalan, thayyiban, and to analyze the relationship between socioeconomic status and consumers’ reason when deciding to buy chicken meat in some markets of Aceh Besar District. This study was conducted from March to April 2016 in Lambaro market, Lam Ateuk market, and Ketapang Dua market. A survey approach was used in this research through interview of respondents using structured questionnaire. The respondents were selected randomly from 139 consumers who buy chicken meat in those markets. The criteria of respondent were Muslim consumers, age ≥ 20 years, and buy chicken meat in the study location. The research data were analyzed descriptively. The results of this study showed that most of the costumer's belief that the chicken meat was sold with halal standard. The majority of consumers mentioned that their beliefs was based on the basis of knowing the butcher which is a Muslim (36.69%). In addition, most consumers ( 90%) expressed confidence in the status of thayyiban (safe, healthy and intact) of broiler chicken which sold in all three markets. Age, level of education, and occupation are the factors that affect the mindset of consumers perception in choosing chicken meat that halal thayyiban. On the other hand, the economic status of consumers also can affect the consideration of the halal, thayyiban, when buying chicken at the market. In conclusion, the status of halal and thayyiban of broiler chicken meat is very important for consumers.